OPTIMAL WAYS TO IMPROVE WOMEN'S SOCIAL MOBILITY MECHANISMS (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2024)
This article provides information about the sources of social mobility, the motivation to achieve, the law of increasing needs, and the hierarchical system of distribution of social results. The presence of channels of social mobility in society, including various social institutions - the military, religion, education, political organizations, trade unions, family, marriage, art, sports, inheritance, elections, mass media, social networks, social networks of individuals and their groups. creates conditions for movement.